2001
DOI: 10.1071/pp00101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell wall hardening and cell wall enzymes of salt-stressed maize (Zea mays) leaves

Abstract: It has been indicated that salinity inhibits maize (Zea mays L.) leaf growth and leaf cell expansion by increasing the apparent yield threshold of the cell wall. We tested whether this increase in the apparent yield threshold was a physical property of cell walls, using in vitro creep-type assays. Salinity had no significant effects on cell wall structural properties based upon several different in vitro assays. In support of these results, there were no differences between control and salt-stressed plants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Neither Hernández et al (2001) nor Cramer et al (2001) reported changes in apoplastic SOD or POX activity (respectively) in salt-treated plants. In contrast, Botella et al (1994) reported NaClinduction of a peroxidase involved in lignification.…”
Section: Antioxidant Activity In Apoplastic Fluidmentioning
confidence: 81%
See 1 more Smart Citation
“…Neither Hernández et al (2001) nor Cramer et al (2001) reported changes in apoplastic SOD or POX activity (respectively) in salt-treated plants. In contrast, Botella et al (1994) reported NaClinduction of a peroxidase involved in lignification.…”
Section: Antioxidant Activity In Apoplastic Fluidmentioning
confidence: 81%
“…The effects of salinity on antioxidant activity has been the subject of much research (Arbona et al, 2003;Menezes-Benavente et al, 2004;Mittova et al, 2004), and some studies have specifically focused on apoplastic components (Cramer et al, 2001;Hernández et al, 2001;Aktas et al, 2005) but general conclusions cannot be drawn due to the diversity of experimental systems and results. Neither Hernández et al (2001) nor Cramer et al (2001) reported changes in apoplastic SOD or POX activity (respectively) in salt-treated plants.…”
Section: Antioxidant Activity In Apoplastic Fluidmentioning
confidence: 99%
“…In leaves of C. gayana grown under saline conditions, a reduction in the length of the EZ was observed, as were increases in the activity of peroxidases and in the phenolic compounds of the cell walls (Ortega et al, 2006). However, Cramer et al (2001) did not find increased wall stiffening or stimulated peroxidase activity under salinity. Erdei and Taleisnik (1993) reported that NaCl treatments had opposite effects on the estimated bulk modulus of elasticity of maize and sorghum leaves: it increased in maize, indicating cell walls became more rigid, and decreased in sorghum, suggesting the opposite.…”
Section: Article In Pressmentioning
confidence: 84%
“…In addition to physiological alterations, adjustment to water limitations is associated with enhanced cell wall thickness and tighter packing of mesophyll cells to resist lower water potentials (Lu & Neumann 1998; Wu & Cosgrove 2000; Cramer, Schmidt & Bidart 2001; Grill et al. 2004).…”
Section: Adjustment To Multiple Environmental Factors In Plant Canopiesmentioning
confidence: 99%